2017
DOI: 10.5603/kp.a2017.0097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic relevancy of left ventricular trabeculation assessed by cardiac magnetic resonance in patients with dilated cardiomyopathy

Abstract: A b s t r a c t Background and aim:We sought to search for factors associated with the magnitude of trabeculation by cardiac magnetic resonance, and evaluate the impact of trabeculations on outcomes in patients with dilated cardiomyopathy (DCM). Methods:We evaluated clinical profiles and outcomes of 276 subjects with DCM (age: 33.2 ± 13.3 years, 160 males). Trabeculation was quantified as trabeculated/total myocardial mass ratio (TM/M). Subjects were stratified into three subgroups (A, B, and C) according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…In our study, LGE was noted in 25% of patients with LVNC, which is similar to data reported by Cheng et al and Nucifora et al, who demonstrated the same prevalence of LGE in their cohorts [19,20]. The percentage of adults with LVNC in whom LGE is recorded varies; however, typically it is more commonly observed and the reported prevalence ranges between 13 and 55% [17,[45][46][47][48][49]. The distribution of LGE is diverse-in the majority of patients it is mid-myocardial; however, subendocardial, subepicardial, and transmural LGE is also described.…”
Section: Fibrosis In Pediatric Lvncsupporting
confidence: 90%
“…In our study, LGE was noted in 25% of patients with LVNC, which is similar to data reported by Cheng et al and Nucifora et al, who demonstrated the same prevalence of LGE in their cohorts [19,20]. The percentage of adults with LVNC in whom LGE is recorded varies; however, typically it is more commonly observed and the reported prevalence ranges between 13 and 55% [17,[45][46][47][48][49]. The distribution of LGE is diverse-in the majority of patients it is mid-myocardial; however, subendocardial, subepicardial, and transmural LGE is also described.…”
Section: Fibrosis In Pediatric Lvncsupporting
confidence: 90%
“…We calculated the hazard ratios of the noncompaction degree for MACE in the patients who met the Peterson criteria ( n = 133), and came to a consistent result: there was no significant correlation between the degree of noncompaction and the incidence of MACE. However, other previous studies showed that the NC/C ratio, segments, and mass of noncompaction were independent predictors of LV systolic dysfunction 22,23 . Therefore, the effect of the degree of noncompaction on prognosis needs further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…Обна-ружение отсроченного накопления гадолиния и его клиническое значение было ранее изучено в качестве предиктора будущих сердечных событий у пациентов с дилатационной кардиомиопатией [13][14][15]. В 2018 г. были опубликованы результаты мета-анализа С. Grigoratos, включавшим в себя 4 исследования [16][17][18][19]. У пациентов с НКЛЖ, включенных в данный мета-анализ [20], отсроченное накопление гадолиния в миокарде ассоциировалось с прогностически неблагоприятным течением заболевания и являлось предиктором серьезных неблагоприятных сердечно-сосудистых событий, таких как сердечная смерть, ишемический инсульт, фибрилляция желудочков, госпитализация по поводу сердечной недостаточности.…”
Section: Discussionunclassified